(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In the current examination, an effort has been made to look into and examine the mechanical characteristics of stir cast composites manufactured from Cu+10wt% Sn alloy reinforced with graphene and Aluminum Oxide metal matrix. In this investigation, Cu+10wt% Sn Alloy was employed as the basic matrix and reinforcements included graphene and aluminium oxide particles. Casting in carried out in 3 different steps 2 wt. % of Gr and Al2O3 were added in to the basic matrix the hybrid composite is being prepared second and third casting of Cu+10wt% Sn alloy+ Gr and Cu+10wt% Sn alloy+ Al2O3 as reinforcements, namely Gr and Al2O3, were warmed to a temperature of 400 degrees Celsius and disseminated. Utilizing optical microscopy, the microstructural investigation produced a matrix alloy with uniformly distributed reinforced particles. The goal was to look at the viability of the method and the mechanical characteristics that would result, such as ultimate tensile strength, yield strength and hardness. The findings showed that adding Gr and Al2O3 particles to Cu-Sn alloy significantly improved the composite's mechanical characteristics.